2004
DOI: 10.1385/mb:26:2:101
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of the Thermostable α-Amylase Gene From <I>Pyrococcus woesei</I> in <I>Escherichia coli</I> : Isolation and Some Properties of the Enzyme

Abstract: Pyrococcus woesei (DSM 3773) alpha-amylase gene was cloned into pET21d(+) and pYTB2 plasmids, and the pET21d(+)alpha-amyl and pYTB2alpha-amyl vectors obtained were used for expression of thermostable alpha-amylase or fusion of alpha-amylase and intein in Escherichia coli BL21(DE3) or BL21(DE3)pLysS cells, respectively. As compared with other expression systems, the synthesis of alpha-amylase in fusion with intein in E. coli BL21(DE3)pLysS strain led to a lower level of inclusion bodies formation-they exhibit o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 9 publications
2
21
0
1
Order By: Relevance
“…The PFA puriWed by alkaline method showed a half-life of 3 h at 120°C and retained over 10% of its maximal activity even after 40 min of incubation at 128°C (Fig. 5b), which were similar to the results reported before [7,8,10].…”
Section: Thermal Stabilitysupporting
confidence: 86%
See 1 more Smart Citation
“…The PFA puriWed by alkaline method showed a half-life of 3 h at 120°C and retained over 10% of its maximal activity even after 40 min of incubation at 128°C (Fig. 5b), which were similar to the results reported before [7,8,10].…”
Section: Thermal Stabilitysupporting
confidence: 86%
“…Results have shown that coexpression of PFA with thioredoxin in E. coli at 18°C is able to diminish inclusion body formation [5], and fusion expression of PFA with intein in E. coli also lead to a lower level of inclusion body formation [7]. However, all these soluble expressions resulted in the lower levels of total recombinant protein production.…”
Section: Introductionmentioning
confidence: 99%
“…O uso direto dos organismos hipertermófilos para produção das enzimas tem se mostrado inviável, em função das dificuldades de cultivos dos mesmos e baixa expressão dos genes envolvidos. A alternativa que se busca é a expressão desses genes em organismos mais adaptados a processos fermentativos industriais, como Escherichia coli ou leveduras 11,90 . Os fungos, embora sejam organismos eucarióticos e, portanto, com termofilia moderada, são também bons produtores de amilases termoestáveis.…”
Section: Amilases Termoestáveisunclassified
“…For example, the recombinant form of a putative extracellular ␣-amylase (PF0477), which produces maltooligosaccharides from starch, has been characterized (9, 25), and an ␣-amylase closely related to PF0477 was characterized from the related species, P. woesei (13,18,27). In addition, an extracellular starch-hydrolyzing amylopullulanase has been characterized from P. furiosus and from the related hyperthermophile Thermococcus litoralis (7).…”
mentioning
confidence: 99%